Effectıveness of the informal economy in Turkey - Takim, Abdullah (EuroJournals, Inc., 2011)
Notwithstanding the differences in the level of development and economic structure, the phenomenon of the informal economy continues to be a common problem in all countries. How to cope with the informal economy and enjoy control over it are priorities in the economic policies. This study first provides short descriptions of the reasons, effects, and measurement methods of the informal economy, which has had adverse effects on competitive power and presents a significant obstacle for funding public spending. The study then attempts to determine the volume of the informal economy as a main focus by making use of tax inspections. © 2020 Elsevier B.V., All rights reserved.
Keywords: Informal; Informal Economy; Taxation Approach; Turkey